2015
DOI: 10.1155/2015/192761
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Bone Alterations in Gaucher Disease: The Role of Immune System

Abstract: Gaucher, the most prevalent lysosomal disorder, is an autosomal recessive inherited disorder due to a deficiency of glucocerebrosidase. Glucocerebrosidase deficiency leads to the accumulation of glucosylceramide primarily in cells of mononuclear-macrophage lineage. Clinical alterations are visceral, hematological, and skeletal. Bone disorder in Gaucher disease produces defects on bone metabolism and structure and patients suffer from bone pain and crisis. Skeletal problems include osteopenia, osteoporosis, ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 55 publications
1
36
0
Order By: Relevance
“…The bone lesions in Gaucher disease are caused mainly due to alterations in its metabolism (turnover, remodeling, and mineralization), leading to various skeletal complications such as osteoporosis, marrow infiltration, avascular necrosis or osteolysis. 4 Patients with preexistent skeletal complications tend to suffer episodes during ERT, such as medullary infarctions, avascular necrosis, or fractures, but the frequency of these occurings is reduced. 3 In our case, the patient had aseptic necrosis of the right femoral head and iliac bone that was treated surgically with total hip replacement shortly after being started on ERT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bone lesions in Gaucher disease are caused mainly due to alterations in its metabolism (turnover, remodeling, and mineralization), leading to various skeletal complications such as osteoporosis, marrow infiltration, avascular necrosis or osteolysis. 4 Patients with preexistent skeletal complications tend to suffer episodes during ERT, such as medullary infarctions, avascular necrosis, or fractures, but the frequency of these occurings is reduced. 3 In our case, the patient had aseptic necrosis of the right femoral head and iliac bone that was treated surgically with total hip replacement shortly after being started on ERT.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, despite the low risk of early failure due to aseptic loosening, total hip replacement in patients with Gaucher's disease with symptomatic osteonecrosis of the femoral head is advised. 4 On an additional matter, patients with GD suffer from early osteopenia. The bone mineral density tends to increase during ERT but with a slow rate, hence early diagnosis and treatment becomes important, in order to avoid severe complications.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some patients are asymptomatic. On a global scale, a study demonstrated that 62% of the patients with GD exhibited a radiological finding of bone involvement while 43% reported pain (8). The Erlenmeyer flask deformity, which is a significant radiological finding, © C I C E d i z i o n i I n t e r n a z i o n a l i starts in the pre-puberty period and is observed in 80% of the adults.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
“…On the other hand, it has been demonstrated that GCase deficiency is associated with increased osteoclastogenesis and bone resorption both in in vitro models and patients' samples. In GD type 1, the number of cytotoxic T lymphocytes was found to be significantly lower in patients presenting bone involvement, and this correlated with higher levels of plasma tartrate resistant acid phosphatase (TRAP) activity, a putative marker of osteoclast cell activity [7][8][9]. Components of the RANKL/RANK/OPG pathway, consisting of the cytokine receptor activator of nuclear factor kappa-B ligand (RANKL), its signaling receptor, receptor activator of NF-κB (RANK), and the soluble decoy receptor osteoprotegerin (OPG) have been shown to be major effectors at multiple levels of the bone regeneration cycle and act as interfaces between immune and skeletal systems [10][11][12].…”
Section: Introductionmentioning
confidence: 99%